2020
DOI: 10.2903/j.efsa.2020.5947
|View full text |Cite
|
Sign up to set email alerts
|

Calcium l‐methylfolate as a source of folate added for nutritional purposes to infant and follow‐on formula, baby food and processed cereal‐based food

Abstract: Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver a scientific opinion on the extension of use of calcium L-methylfolate to be used as a source of folate added for nutritional purposes to infant and follow-on formula, baby food and processed cereal-based food pursuant to Regulation (EU) 609/2013. In 2004, EFSA assessed the use of calcium L-methylfolate as a source of folate in foods for particular nutritional uses, food supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…For this scientific assessment, a protocol (Appendix A) has been developed in line with existing methodology (EFSA, 2020).…”
Section: Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For this scientific assessment, a protocol (Appendix A) has been developed in line with existing methodology (EFSA, 2020).…”
Section: Methodologiesmentioning
confidence: 99%
“…EFSA AFC Panel (2004) and EFSA NDA Panel (2020) The EFSA Panel on Food Additives, Flavourings, Processing Aids and Materials in Contact with Food (AFC) and the EFSA NDA Panel assessed the safety of CaLMF for addition to foods. With respect to bioavailability, the AFC Panel concluded that in aqueous media, CaLMF dissociates readily and completely into Ca and L-5-MTHF ions and that its bioavailability is similar or even slightly higher than that of folic acid (EFSA AFC Panel, 2004), while the NDA Panel confirmed that CaLMF is a source from which folate is bioavailable (EFSA NDA Panel, 2020).…”
Section: Efsa Ans Panel (2013)mentioning
confidence: 99%
“…However, infants receiving formula containing 5-methyl-THF had lower UMFA levels in plasma (0.73 vs. 1.15 nmol/L, p < 0.0001) than infants fed with folic-acid-fortified formula [ 37 ]. As supported by its safety, high proportion in breast milk and clinical studies, 5-methyl-THF has already been approved as a source of folate in infant formulas by the EFSA [ 38 ]. The reduced folate accounted for 87.9~97.0% of the total folate in breast milk at all lactating periods, in which 17.0~31.9% was the minor reduced folate.…”
Section: Discussionmentioning
confidence: 99%
“…Diets were custom made by Research Diets Inc. (New Brunswick, NJ, USA) ( Supplementary Materials Table S1 ) and stored at 4 °C and in the dark until provided fresh weekly. The additions of the MTHF form of folate into foods has been shown to be stable at both 4 °C and room temperature for up to 24 months [ 39 ]. Analytical testing of the high folate diets following a 36-month storage at −80 °C showed >80% retention of folates ( Table S1 ), further confirming their long-term stability.…”
Section: Methodsmentioning
confidence: 99%